Systemic immune inflammation index as a useful prognostic indicator in the prediction of chronic aphthous stomatitis - Kolenko Юлія Геннадіївна; Synko Альона Олегівна; Gryg Наталія Іванівна (Actual Dentistry, 2024)
Relevance. Chronic recurrent aphthous stomatitis (RAS) is one of the most common chronic inflammatory diseases of the oral cavity, which affects approximately 5 to 25% of the population. RAS is a multifactorial disorder, and studies have pointed to several potential causes associated with its occurrence. The aim is to analyse the role of inflammatory markers in the development of chronic recurrent aphthous stomatitis. Materials and methods. The study involved 80 patients: 29 men (36.25%) and 51 women (63.75%) with RAS who sought help at the Department of Therapeutic Dentistry of the Bogomolets National Medical University. The ulcer severity score (USS) was used to assess and monitor the ulcers according to 6 clinical characteristics: number of ulcers, size of ulcers, duration of ulcers, period without ulcers, pain and location of ulcers. NLR, PLR and SII values were calculated from the results of a complete blood count. The measurements were compared statistically using SPSS software (version 23.0 for Windows). Study results and discussion. The mean USS score was 35.8±7.78 in patients with RAS. NLR values were significantly higher in patients with RAS than in the control group (3.59 ± 2.9 vs. 1.76 ± 2.4, p < 0.001). The values of SII and PLR were statistically higher in patients with RAS compared with the control group (SII, 606.0 ± 2.9 vs. 409.8 ± 2.1 kl/l, p < 0.001; PLR, 192.3 ± 1.9 vs. 105.9 ± 0.96, p = 0.01). Conclusions. NLR, SII, PLR are cheap and simple biomarkers that can be used as markers of inflammation or severity of inflammation in patients with RAS. Key words: chronic aphthous stomatitis, blood, neutrophils, leukocytes, platelets, inflammation, systemic immune inflammation index.